Peach Gum Polysaccharide Prevents Chemotherapy-Induced Intestinal Injury and Degenerative Behavior - Jiaqi Cui MM; Wuhong Wang MM; Zhongjia Yi MM; Huan Tian MM; Hui Wang MM; Chunyun Jiang Bmed; Yiliu Chen PhD; Dajin Pi PhD; Qianjun Chen MD, PhD; Yingchao Wu MD, PhD (Integrative Cancer Therapies)
This study investigated the effects of peach gum polysaccharide (PGP) on chemotherapy-induced intestinal injury and behavioral changes in mice. Female C57BL/6 mice were injected with E0771 breast cancer cells and divided into 3 groups: control, chemotherapy (pirarubicin), and PGP treatment (pirarubicin plus PGP). Behavioral tests, colon length measurement, tissue staining, 16S rDNA sequencing, and metabolomics were performed. Transcriptomic data of colon and hippocampal tissues were analyzed and validated by Western blotting. PGP significantly alleviated colon damage, reduced inflammation and apoptosis, and restored colon length. It mitigated depressive behaviors by suppressing inflammasome activation in the hippocampus, increased gut microbiota diversity, and improved depression-associated metabolites. After the depletion of the intestinal flora, the antidepressant effect of PGP is significantly weakened. These findings suggest that PGP protects against chemotherapy-induced intestinal and behavioral damage by modulating the gut microbiota and gut-brain axis.